Suitability of pineapple leaf fiber for the reduction of noise in aircraft power plants. (August 2019) - Manigandan, S.; Ramanathan, Muthiaya; kumar, Dinesh; Nithya, S.; Gunasekar, P.; Devipriya, J.
Abstract: The application of natural fiber replacing metals is growing rapidly. Among the various natural fibers pineapple leaf fiber gaining the attention of pioneers due to its high strength and deformation resistance. This paper studies the effect of pineapple fiber when the mixed with graphene nanocomposites for the aerospace applications. Pineapple leaf fibre (PLF) is well-known natural fiber for its rich cellulose content. Moreover, this paper studies the topological properties of Pineapple leaf graphene fiber. Additionally the noise and vibration absorption capacity of the fiber also calibrated. During the operation of aircraft power plant the unwanted acoustic noise generated by the aircraft is massive. Usually, these noises are not absorbed by metal bodies. These unwanted noises will aid passenger discomfort. The test relieves the homogenous pineapple fiber doesn't show a profound effect in absorbing the noise and vibration. This drawback is overcome by adding nanoparticle graphene. The graphene is mixed with epoxy in three varies in proportions 3%, 4% and 8% to form tested specimen P3, P4 and P8. From the results, it is clear that P8 shows an intense effect in the increase of strength to weight noise and the noise characteristics nearly 18% compared to other fibers.